(untitled) (Altre Modernità, 2019)
What follows is a qualitative analysis of the use of impoliteness for comic effect in the British comedy series Life’s Too Short written by Ricky Gervais and Stephen Merchant. Because each episode centres on Warwick Davis, an actor with restricted growth, or dwarfism, there is a considerable risk of superiority or disparagement-type comedy about a taboo subject like physical difference, stigmatized in current British culture. In this analysis I set out to show that the authors’ use of impoliteness plays an important role in allowing them to write comedy centred on this sensitive issue. The starting-point of the analysis is Culpeper’s proposal that impoliteness can be entertaining, which in this case is applied to scripted comedy rather than impromptu or semi-spontaneous examples of impoliteness for purposes of entertainment. Referring to aspects of impoliteness applied to entertainment, and with reference to the concept of face, and to superiority, incongruity, and relief humour theories, the paper suggests there are at least six techniques by which the authors use impoliteness to reprise physical difference for a contemporary comedy series.